Kecerdasan Majemuk dalam Pembelajaran Bahasa Arab - Rahma, Husnul Hafiza; Mufidza, Shafira; Mu'jizah, Anis Anfa'atul (Tadabbur: Jurnal Integrasi Keilmuan, 2024)
Education is one of the most important indicators in forming a perfect human being. In humans, there must be talents, interests, and intelligence whether realized or not, where basic intelligence describes the nature and identity of humans. Intelligence can develop in line with human interaction with their environment. In other words, humans have the ability to learn and increase their intelligence potential. The purpose of this study is to find an Arabic language learning method based on the concept of multiple intelligences. The variety of ways students learn indicates that humans have more than one intelligence. Among them are IQ (Intellectual Intelligence), SQ (Spiritual Intelligence), EQ (Emotional Intelligence), and PQ (Physique Intelligence).1 This is what is called multiple intelligences in which the role of teachers is very much needed because when the learning process takes place there is a process of teachers teaching and students learning. Teachers are required to be able to combine the right methods so that learning objectives can be achieved. This study uses a qualitative method with descriptive analysis, namely by describing multiple intelligences in Arabic language learning. The results of this research show that multiple intelligences influence Arabic language learning in developing language skills, including maharatul istima', maharatul kalam, maharatul qira'ah, maharatul kitabah.